Trends and evolution in the concept of historical towns sustainability - Moscatelli, Alessandra; Buonocore, Elvira; Fullana-i-Palmer, Pere; Franzese, Pier Paolo (Ecological Questions, 2023)
The present study aims to review the scientific literature on sustainable towns by tracking its evolution and trends, with reference to the Sustainable Development Goals localization, and by applying social network analysis to bibliometric science. The bibliometric analysis, implemented over the timeframe 1996-2021, allowed the generation of maps based on network data displaying the relationships among scientific journals, researchers, and countries. Two different bibliometric analyses were performed to explore the scientific literature on “sustainable historical towns” and “sustainable towns’ assessment”. The results were useful to capture the multidimensional nature of sustainable towns by analyzing a large amount of literature data while identifying the main scientific patterns in this field of science. The paper is organized as follows. Sections 1 and 2 briefly introduce the topic and goal of the study. In section 3, the concept of “historical town” is defined by a qualitative and quantitative analysis. In section 4, governance issues related to small size municipalities are described with a focus on the inner peripheral areas. In Section 5, a review of sustainable urban policy evolution at the global and European levels is presented. Section 6 illustrates the state of the art in sustainability assessment of towns, analyzing the main issues and advancements of SDGs localization in the European historical small and medium-sized towns and rural areas. Section 7 illustrates the methodology and results of the performed bibliometric network analysis. Finally, the main findings of the study and research perspectives are summarized in Section 8.